The teacher as persuader: On the application of Wittgenstein’s notion of ‘persuasion’ in educational practice - Ariso Salgado, José María (Routledge, 2022)
Wittgenstein’s conception of ‘persuasion’, understood as the persuader’s attempt to modify the persuadee’s certainties, has been recently misinterpreted by some scholars. For Persichetti has overlooked the fact that one cannot persuade unintentionally, while Marconi and Perissinotto have not only taken for granted that persuasion consists in the mere transfer of a world-picture or set of certainties to an individual even when she has not alternative or different certainties, but also that education is restricted to persuading or transmitting certainties. After clarifying these misinterpretations, among others, I argue that persuasion is not used for teaching certainties at the outset, but for modifying them when they do not fit the ones expected by the persuader. If it is agreed that education partly consists in transmitting a world-picture, then persuasion constitutes a necessary resource for educators. Lastly, I provide a set of guidelines for teachers to draw attention to the basic aspects of persuasion that they should consider in the classroom. © 2021 Philosophy of Education Society of Australasia.
Keywords: certainty; education; Persichett; persuasion; Wittgenstein; Scopus; JCR